Gambaran Karies Gigi Sulung pada Anak Stunting di Indonesia - Aviva, Novia N.; Pangemanan, Damajanty H. C.; Anindita, Pritartha S. (e-GiGi, 2020)
Abstract: Dental caries, as well as stunting in children, is still a worldwide problem including in Indonesia. Malnutrition can cause stunting and abnormal growth and development of teeth causing the child's teeth become more susceptible to caries. This study was aimed to obtain the description of primary dental caries among stunting children in Indonesia. This was a literature review study. Three databases used in this study, as follows: Pubmed, ClinicalKey, and Google Scholar. The keywords were stunting AND caries AND Indonesia. After being selected based on inclusion and exclusion criteria, a critical appraisal was carried out that obtained 5 literatures consisting of 4 cross-sectional studies and 1 cohort study. The results showed that stunting children had higher percentage of primary dental caries than normal children, with moderate to high caries severity reaching 80%. Children who suffered from high dental caries severity had a high chance of suffering from stunting in the future. In conclusion, stunting children in Indonesia suffered from caries of primary teeth categorized as high severity caries. There was a relationship between caries of primary teeth and stunting in children.Keywords: Primary dental caries, stunting, child.Â Abstrak: Seperti halnya karies gigi, stunting pada anak masih menjadi masalah dunia termasuk Indonesia. Kekurangan gizi pada masa-masa kritis dapat menyebabkan stunting pada anak serta tumbuh kembang gigi yang tidak normal sehingga gigi anak lebih rentan mengalami karies. Penelitian ini bertujuan untuk mengetahui gambaran karies gigi sulung pada anak stunting di Indonesia. Jenis penelitian ialah studi pustaka. Pencarian data menggunakan tiga database yaitu Pubmed, ClinicalKey, dan Google Scholar. Kata kunci yang digunakan yaitu stunting AND caries AND Indonesia. Setelah diseleksi berdasarkan kriteria inklusi dan ekslusi, dilakukan critical appraisal dan didapatkan 5 literatur terdiri dari 4 cross-sectional study dan 1 cohort study. Hasil penelitian menunjukkan anak stunting memiliki pengalaman karies gigi sulung lebih tinggi daripada anak normal dengan tingkat keparahan karies sedang sampai tinggi mencapai 80%. Anak yang menderita pengalaman karies gigi sulung parah, memiliki peluang tinggi menderita stunting di kemudian hari. Simpulan penelitian ini ialah anak stunting di Indonesia memiliki pengalaman karies pada gigi sulung dan terbanyak pada tingkat keparahan karies yang tinggi. Terdapat hubungan antara karies pada gigi sulung dan stunting pada anak.Kata kunci: karies gigi sulung, stunting, anak.